2016
DOI: 10.1080/01496395.2016.1221432
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon nanofiber produced from electrospun PAN nanofiber as a solid phase extraction sorbent for the preconcentration of organophosphorus pesticides

Abstract: Activated carbon nanofibers (CNFs) were derived from electrospun nanofibers with subsequent heat treatment. They were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. The applicability of activated CNFs for preconcentration and determination of organophosphorus pesticides (OPPs) was investigated by high-performance liquid chromatography with diode array detector (HPLC-DAD). Some important parameters influencing the extraction efficiency, such as amount of sorbent, pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…While a large number of biopolymers can be electrospun from water [6,7], only few waterresistant polymers can be spun from low-toxic solvents such as dimethyl sulfoxide (DMSO) [8]. Th is is one of the reasons why polyacrylonitrile (PAN) is of large interest in electrospinning, apart from its usability as a precursor for carbon nanofi bres [9][10][11]. Preliminary tests in our group showed that animal cells do not grow well on pure PAN nanofi brous mats although serum was added to the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…While a large number of biopolymers can be electrospun from water [6,7], only few waterresistant polymers can be spun from low-toxic solvents such as dimethyl sulfoxide (DMSO) [8]. Th is is one of the reasons why polyacrylonitrile (PAN) is of large interest in electrospinning, apart from its usability as a precursor for carbon nanofi bres [9][10][11]. Preliminary tests in our group showed that animal cells do not grow well on pure PAN nanofi brous mats although serum was added to the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of antibiotics is one of the preferred approaches to confiscate organic pollutants from water owing to the desirable qualities: ease of operation, low energy cost, and environmental friendliness [19]. Recently, the preparation of polymeric adsorbents for the adsorption of organics has been performed by using the electrospinning method, which is advantageous because of its low cost and simplicity [20]. Electrospinning has become popular for the preparation of nanofibers with attractive electronic properties and large surface-to-volume ratios [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the preparation of polymeric adsorbents for the adsorption of organics has been performed by using the electrospinning method, which is advantageous because of its low cost and simplicity [20]. Electrospinning has become popular for the preparation of nanofibers with attractive electronic properties and large surface-to-volume ratios [20]. Furthermore, the use of electrospun nanofibers has been employed in different fields, including the removal of inorganic and organic pollutants in water [21].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylonitrile (PAN) is a material that can be dissolved in dimethyl sulfoxide (DMSO), a solvent that must be handled with care, but does not cause problems in biological or medical applications. PAN is thus a typical material used in electrospinning [1,2]. In most cases, it is used in a two-step process for the creation of carbon nano bres [3][4][5].…”
Section: Introductionmentioning
confidence: 99%